2020
DOI: 10.1149/2162-8777/aba1cc
|View full text |Cite
|
Sign up to set email alerts
|

Review—A Survey of Simulations on Device Engineering of GaN-Based Light-Emitting Diodes

Abstract: In InGaN-based light-emitting diodes, efficiency droop at high current density degrades device performance. Different strategies have been proposed by researchers to enhance the performance of InGaN-based light-emitting diodes numerically. We present a survey of the notable reported efficient simulated device structures, to date. We also discuss the simulation methodology employed in the state-of-the-art numerical simulators to study InGaN-based light-emitting diodes. Our survey gathers the influence of the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 93 publications
0
5
0
Order By: Relevance
“…However, very few direct measurements of either mechanism are published, none of which establishes a dominating magnitude. Most publications on efficiency droop mechanisms base their quantitative claims on modeling and simulation [ 4 , 7 , 8 ]. Nevertheless, the total energy efficiency is usually of greater importance [ 9 ] and it is the focus of this paper.…”
Section: Introductionmentioning
confidence: 99%
“…However, very few direct measurements of either mechanism are published, none of which establishes a dominating magnitude. Most publications on efficiency droop mechanisms base their quantitative claims on modeling and simulation [ 4 , 7 , 8 ]. Nevertheless, the total energy efficiency is usually of greater importance [ 9 ] and it is the focus of this paper.…”
Section: Introductionmentioning
confidence: 99%
“…Basically, the difference in temperature of 1°C at a surface could induce a shift in emission wavelength of ≈1.8 nm in the case of blue LEDs and 2.5 nm in the case of green LEDs. [54,55] To address these problems, a number of solutions have been proposed, e.g., Lu et al reported the uniform emission with ≈2 nm deviation by implementing the proper pocket design for 2, 4, and 6 in. wafer.…”
Section: Epitaxial Growth and Chip Processing Of Ledsmentioning
confidence: 99%
“…In III-Nitrides semiconductors, the asymmetrical behavior of electrons and holes, such as the difference in their effective mass and mobility, deteriorates the performance of devices [123]. Because of that, the concentration of carriers is not uniformly distributed inside of the QW region.…”
Section: Qw and Qb Roles In Uv Emissionmentioning
confidence: 99%